The Study of Facial Pain in A Practice of Dentist - Burxonova Zarafruz Qobilovna; Zulpanova Dinara; Maxmudova Sevara; Istamova Vazira (Genius Publishing Group, 2024)
In clinical practice, dentists and neurologists often encounter facial pain of varying severity, localization and duration. The various etiologies and pathologies of pain symptoms, combined by the term "facial pain", reflect the anatomy and physiology of vegetative and somatic innervation of facial tissues. Differential diagnosis is fraught with great difficulties and is often erroneous
Keywords: Odontogenic diseases; dentists and neurologists